Exchange Rate Fluctuations and Sectoral Performance of the Nigerian Economy (1980- 2016) (European Journal of Marketing and Economics, 2020)
The structure of Nigerian economy has changed considerably over the years. The economy is classified into five interrelated sectors; the agriculture, Industry, construction, trade and services (CBN 2016). Some of these sectors have contributed to the national output and government revenue at different point in time. Different exchange rate regimes implemented in the country have had varying degrees of impact on the performance of the economic sectors. Depending on the foreign exchange component of inputs into the various sectors and the export earning potential of each sector, sectoral performance has shown high level of sensitivity to exchange rate fluctuations. Fluctuations in exchange rate affect the cost of production in the various sectors of the economy. It is, therefore, not surprising that exchange rate is among the most watched, analysed and government manipulated macroeconomic indicator as it plays a vital role in a country’s level of trade, which is critical for every free market economy in the world. This paper is a review of the performance of the Nigerian economy in the light of the volatility of exchange rates in Nigeria.
Keywords: Exchange Rate Fluctuations, Sectoral Performance, Nigerian Economy